Concept, types, genres, and functions of cinema art - Gayratovna, Jabborova Aziza (Goodwood Publishing, 2025)
Purpose: This study aims to explore the philosophical essence and evolution of cinema as a form of artistic expression that reflects and transforms human perception of reality. It examines how cinema functions not only as entertainment but also as a socio-cultural medium that mirrors moral, aesthetic, and ideological transformations in modern society. Research Methodology: The research adopts a qualitative and interpretative approach, combining philosophical analysis, semiotic interpretation, and comparative cultural study. It involves textual examination of selected film genres and theoretical literature to uncover how cinematic representation mediates between art, society, and human consciousness. Results: The findings reveal that cinema serves as both a mirror and a catalyst of social change. Thematic and stylistic evolution in film correlates with shifts in collective consciousness, values, and identity. Moreover, the study identifies how technological innovation has reshaped the perception of reality through moving images, intensifying emotional and symbolic engagement. Conclusions: Cinema functions as a dynamic system of meaning-making that reconstructs reality through the lens of cultural experience. It unites artistic creativity with philosophical inquiry, contributing to the understanding of how modern individuals interpret existence through visual narratives. Limitations: The study is limited to interpretative analysis of theoretical and artistic texts, without empirical audience data or statistical validation. Contribution: This article enriches the field of film philosophy and cultural theory by linking aesthetic functions of cinema with philosophical discourse on human perception and modernity.